Teething problems in materials development for teaching social interaction skills in English - Ting, Su Hie; Diana, Carol (2006)
Choosing the right materials to achieve learning outcomes and to meet the diverse needs ofleamers is difficult. The level may not be right, the context may not be j1imiliar or the language skills focused on may not be on target. Designing new materials may seem to be the solution but it gives rise to other problems that prevent these materials from achieving intended purposes. This study aimed to examine the initial problems in materials design and use for an English for Social Purposes course which focuses on the listening and speaking skills. The objectives of the study were to examine: (1) aspects ofthe materials that instructors were able or unable to use as intended; and (2) areas overlooked in the design of the materials. The pedagogical framework for the materials was the genrebased approach and the concept of scaffolding. The materials were used by 22 instructors teaching 34 groups of about 850 undergraduates. Data for the materials evaluation were obtained from instructors' feedback and observations of how the materials were used in class. The results revealed two unanticipated problems, that is, the inability of instructors to elaborate on the social contexts of given situations, and their misguided knowledge of language pedagogy. This paper concludes with measures to improve the materials for the second cycle ofthe curriculum implementation.